POROSITAS KAYU JATI KLON CEPU DAN MADIUN UMUR 7 TAHUN - Andi Detti Yunianti (Forestry Faculty of Universitas Hasanuddin, 2012)
This study was aimed at determining the pore characteristic (type, dimension and frequency of vessel) of teak from different clones (Cloned Cepu and Madiun). For the purpose of the study, teak wood samples with the age of 7 years were taken from research site number 22a of RPH Banaran, BKPH Playen, Gunung Kidul, in Watu Sipat Forests, Biotechnology and Forest Tree Improvement Research Facilities in Yogyakarta at different planting distances (3 m x 3 m and 2 m x 6 m). Results show that the type of pores is diffuse-porous until the 3th growth ring and after that; it becomes semi ring-porous. The variation of diameter, length and frequency of vessels from cloned Cepu and spacing 3 m x 3 m are comparatively uniform compared to that of cloned Madiun and spacing 2 m x 6 m. Key words: Cloned teak, pores, planting distance, Cepu, Madiun